Upaya Pengembangan Objek Wisata Air Terjun Sedudo Melalui Pendekatan Community Based Tourism di Desa Ngliman Kabupaten Nganjuk - Juwita Marpaung, Vini Febrianty; Nawangsari, Ertien Rining (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article aims to investigate, describe, and analyze initiatives to enhance the Sedudo Waterfall tourist destination by implementing a Community-Based Tourism (CBT) approach in Ngliman Village, Nganjuk Regency. The primary concern lies in the lack of integrated management, posing a hindrance to the progress of Sedudo Waterfall. Despite the natural beauty of the Sedudo Waterfall, there is a notable absence of an effective cleanliness management system. The facilities at Sedudo Waterfall have not received proper upkeep, and the tourist spot lacks cleanliness, evident in dirty seating and scattered waste from food and beverages throughout the area. To address this issue, theoretical foundations from UNEP and WTO are employed, utilizing the five main principles outlined in Community Based Tourism Development by Suansri (2003). Data was gathered through in-depth interviews with various informants at the Nganjuk Regency Culture and subsequently analyzed qualitatively. The study concludes that: achieving the implementation of Community-based Based Tourism at the Sedudo Waterfall tourist attraction is based on economic principles, social principles, cultural principles, environmental principles, and political principles. Although on economic principles there are limited regional government budgets allocated for developing Sedudo Waterfall.